“La imagen institucional del GADM del cantón Chunchi y su incidencia en los habitantes de la matriz en las edades comprendidas de 30 a 60 años, en el periodo enero a diciembre de 2015” - Montero Vivar, Rosa Orfelina (2017)
INSTITUTIONAL IMAGE OF THE AUTONOMOUS MUNICIPAL GOVERNMENT OF THE CHUNCHI CITY, AND ITS INCIDENCE IN THE POPULATION OF MATRIX, BETWEEN THE AGES FROM 30 TO 60, DURING THE PERIOD FROM JANUARY TO DECEMBER 2015. ABSTRACT: Developing and execution of this research, reference has been made to form concepts, theories, postulates and guidelines on the Institutional Image of the Autonomous Municipal Government of the Chunchi city, located in Chimborazo province; and its incidence in the population of Matrix, between the ages from 30 to 60, during the period from January to December 2015. Chapter one, there are clear reviews about the research references that are developed in the approach of the problem. It also establishes the general objective and specific objectives; those are related to the justification, relevance, feasibility, and importance of the topic of study that bases its approach on the described problem. The development of the theoretical foundation is composed for academic theories and pronouncements, which will allow to broaden the scientific, theoretical, conceptual and doctrinal support of the proposed problem. The development of the theme of the Institutional Image of the Municipal Decentralized Autonomous Government of the Chunchi canton, allowed the study about what is the corporate Image, factors, characteristics and importance for the entities development; also, it explains what public opinion is; Communication, and describe its theories. The third chapter, on the other hand, is about the methodological process applied in the implementation of the research, about the gathered information for the performance of the research that allowed verifying the hypothesis, besides building knowledge about the topic. In the fourth chapter, we present the reached conclusions and recommendations, after have complied with research process, and based on the conclusions were established recommendations with the intention to be applied to improve the identity of the Chunchi GAD. The fifth and final chapter presents the Strategic Communication plan for is implementation in GADM Chunchi.